New ICD-11 diagnostic criteria for chronic secondary musculoskeletal pain associated with Parkinson disease - Mylius, Veit; Moisset, Xavier; Rukavina, Katarina; Rosner, Jan; Korwisi, Beatrice; Marques, Ana; Lloret, Santiago Perez; Kägi, Georg; Bohlhalter, Stephan; Bannister, Kirsty; Chaudhuri, Kallol Ray; Barke, Antonia; et al. (Pain, 2024)
An abstract is unavailable.